Exploring the Spectrum of Sulcal and Gyral Morphology in the Human Cerebrum. - Varigeti, Mizoram; Kumar, Abhimanu (Journal of Neonatal Surgery, 2025)
Individual neuroanatomy exhibits considerable variability in the folding patterns of the superolateral cerebral cortex, specifically in its gyri (ridges) and sulci (grooves). While often considered incidental, the clinical relevance of these variations remains largely unexplored. This study investigated the prevalence and types of sulcal and gyral variations on the superolateral cortical surface and initially explored their potential association with neurological history. A detailed cadaveric analysis was conducted on 56 human brains obtained from the Department of Anatomy, JHMC. The superolateral surfaces of both hemispheres were meticulously examined, and any deviations from standard sulcal and gyral patterns were identified and categorized using established anatomical classifications. The study revealed sulcal and gyral variations in 70% of the examined brains, including variations such as Superfrontal Gyral, Inferior Frontal Gyral, Post Central Gyral, Sylvian fissure bifurcation, and atypical frontal gyri. Preliminary statistical analysis explored potential correlations between these specific variations and the documented medical history of the donors, with a focus on neurological conditions. This cadaveric analysis highlights the significant prevalence of sulcal and gyral variations in the human superolateral cortex, underscoring the need for further research to elucidate their precise clinical implications. Future studies with larger, well-characterized cohorts are warranted to investigate potential links between these anatomical variations and neurological function or dysfunction